Perbaikan Postur Kerja pada Proses Mixing di PT. Xc Cleanindo - Farhan, Ahmad Farhan; Baliavi, Fandika; Azmi, Nora; Rahmawat, Novia; Gunawan, Leo Van; Alba Pradana, Claudha (UNISTEK, 2025)
This PT XC CLEANINDO is a manufacturing startup that provides cleaning and sanitation needs. The mixing and packing process in this company has less ergonomic work postures and facilities. Based on the Nordic Body Map (NBM) questionnaire, operators often feel pain in several parts of the body due to non-ideal working postures, especially repeated bending positions during the mixing process which can trigger back injuries. Postural analysis using the REBA and QEC methods showed a high risk score (REBA: 8, QEC: 61.36%). To reduce this risk, it is recommended to modify the manual lift table according to Indonesian anthropometric data. After improvement, the REBA score dropped to 3, indicating significant improvement in working posture, especially in the operator's neck and back. This implementation is expected to increase productivity and worker health.